System for monitoring patients diagnosed with Alzheimer's using wearables (LACCEI, 2024)
Alzheimer's disease is the main cause of dementia, and currently there are more than 60% of cases diagnosed with dementia, likewise, each year about 10 million new patients are diagnosed in the world. (Sánchez Danilo, 2010), a neurologist at the National Institute of Neurological Sciences, mentions that in Peru 10% of the 60-year-old population suffers from Alzheimer's disease and it starts normally in adults over 60. That is why it was proposed to implement a monitoring system for patients with Alzheimer's using wearables from the Xiaomi brand model MI Band 6, since it helps us to collect physical health data. With this we reduce the attention time in a medical appointment. The time it takes to perform the analysis can vary between 7 to 15 days. It is worth mentioning, that within the investigation we have considered in the sample a minimum of 5 patients, 5 neurologists and 5 psychologists. When applying the surveys, according to the 3 indicators proposed, the result for the first indicator "User Satisfaction" was obtained, that 76.67% of those surveyed recommend the application. On the other hand, 25.33% recommend putting instructions for the application. For indicator number 2, "Data Availability", it was obtained that the average time of data availability decreased by 22 days (86.76%). And finally, for "Attention time", the average time in the speed of monitoring decreased by 177.87 hours (39.08%) It was obtained as a result for the first indicator "User Satisfaction", that 76.67% of those surveyed recommend the application. On the other hand, 25.33% recommend putting instructions for the application. For indicator number 2, "Data Availability", it was obtained that the average time of data availability decreased by 22 days (86.76%). And finally for "Attention time", the average time in the speed of monitoring decreased by 177.87 hours (39.08%) It was obtained as a result for the first indicator "User Satisfaction", that 76.67% of those surveyed recommend the application. On the other hand, 25.33% recommend putting instructions for the application. For indicator number 2, "Data Availability", it was obtained that the average time of data availability decreased by 22 days (86.76%). And finally for "Attention time", the average time in the speed of monitoring decreased by 177.87 hours (39.08%)